A Biblioteca como espaço de educação: o letramento de jovens e adultos – projeto “alfabetizar para libertar” - BRITO, Camila de Cássia (Universidade Federal do Pará, 2021)
The current study was carried in the Marajoara Amazon, starting from the realization of the extension project “Literate to free”, from the Professor Ricardo Teixeira de Barros Library, from Marajó University Campus - Soure (UFPA), which proposed to develop reading as a literacy action for Young people and adults away from school life. Reading can be understood as a technique for improving the individual cognitive capacity, being worked based on culture, daily life, memories and experiences and individual and collective experiences. Theoretically, this study is based on the ideas of Freire (1987,1989,1996,1997); Schwartz (2010); Loyal; Albuquerque and Morais (2010), Giubilei (2005); Leite (2013) and Gadotti; Romao (2011). Thus, questionnaire and observation were used as data collection techniques. Study is characterized as action research. The results showed that of the 27 participants in the project, 25 of them improved the practice of reading combined with the practice of 1 Mestranda – PPLSA (UFPA - 2019). Especialista em Gestão de Unidades de Informação (IPGC – 2017). Graduada em Biblioteconomia (UFPA – 2013). Bibliotecária – Documentalista (UFPA – Biblioteca Central) Help Desk do Portal de Periódicos da Capes - Região Norte. E-mail: camilacbrito@ufpa.br. 2 Mestrando – PPLSA (UFPA - 2019). Especialista em Tradução e interpretação do Inglês (FIBRA - 2015) Graduado em Pedagogia (FAEL - 2019). Graduado em Letras (UFPA-2012). Professor de Língua inglesa da Secretaria Municipal de Educação do Município de Salvaterra (Marajó – PA) e Coordenador do Curso de Idiomas na Marajó English School (MES). E-mail: karley@ufpa.br. 3 Doutora e Mestra em Educação pela Universidade Federal do Pará. Docente do Programa de Pós-Graduação Linguagens e Saberes da Amazônia e professora Adjunta da Universidade Federal do Pará Campus de BragançaPa. É membro da Associação Nacional de Pós-Graduação e Pesquisa em Educação. Coordena o Grupo de Pesquisa de Educação de Jovens e Adultos e Diversidade na Amazônia. E-mail:jdneves@ufpa.br. 174 NOVA REVISTA AMAZÔNICA - VOLUME IX - Nº 02 - JUNHO 2021 - ISSN: 2318-1346 writing and 2 of those, learned to read and write. Every action taken in favor of the community is extremely important for the educational scientific field as a whole and extension projects in different educational spaces are welcome as a practice of integration between the University and the academic and external community, providing significant experiences in the lives of these individuals.